A Survey on Reliability Assessment of Power Modules - Khoshzaman, Shima; Hahn, Ingo (2018 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM), 2018)
The continuous increase in the requirements of power modules in industrial applications is the motivation to draw more attention towards reliability and the state-of-health assessment of them. The basics of conventional module packaging technology containing base plate, bond wires and solder layers and its limitations are reviewed in this paper. Typical end-of-life package-related failures are discussed. In addition, accelerated aging tests and common lifetime estimation models are reviewed.<br
Keywords: Power modules; reliability; accelerated aging test; lifetime estimation